A note on the application of wazewski’s topological method to an integro: differential equation of volterra type - Napoles Valdes, Juan Eduardo (2015)
The purpose of this note is to generalize the Wazewski’s Topological Method 11, originally stated for ordinary differential equations, to the integro – differential equation of Volterra type (1), under suitable conditions on the functions involved.